2003
DOI: 10.1046/j.1365-2796.2003.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of proteinuria: the kidney filtration barrier and progressive renal failure

Abstract: The past few years have witnessed a major breakthrough in the understanding of the molecular mechanisms and ultrastructural changes behind the development of proteinuria. The discovery of several proteins in the glomerular podocyte and slit diaphragm, where mutations lead to disease, has revealed the importance of this cell with its diaphragm as the major filtration barrier as opposed to the glomerular basement membrane (GBM) previously ascribed this function. Furthermore, accumulating clinical as well as expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 74 publications
1
76
0
14
Order By: Relevance
“…Podocytes are polarized epithelial cells, with their interdigitating foot processes forming the outer barrier to urine protein as a high-volume/high-discrimination filter, through which the blood is filtered hydrostatically (30). Podocyte dysfunction leads to proteinuria and progression of renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes are polarized epithelial cells, with their interdigitating foot processes forming the outer barrier to urine protein as a high-volume/high-discrimination filter, through which the blood is filtered hydrostatically (30). Podocyte dysfunction leads to proteinuria and progression of renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Further study will be necessary to understand the roles of perlecan core protein in the formation of the kidneys. Recent studies have revealed the important roles of slit diaphragms separating podocyte foot processes as filtration barriers (36,37,38). For instance, genes including NPHS-1 and NPHS-2, identified as responsible for nephrotic syndrome with the Mendelian hereditary trait, are expressed exclusively in slit diaphragms (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular injury leads to increased glomerular permeability to macromolecules, such that albumin and other large serum proteins are able to gain access to the mesangium and tubular fluid. In some morphologic studies, the magnitude of proteinuria or albuminuria is correlated with the magnitude of severity of glomerular and tubulointerstitial damage, as well as GFR decline (32,33). It is well established that proteinuria is part of the natural history of many CKD.…”
Section: Physiologic Basis For Proteinuria and Its Relationship To Kimentioning
confidence: 99%